CONDUCTING APPRAISAL AND PERFORMANCE OF COMMERCIAL BANKS IN MACHAKOS COUNTY- KENYA - Mutindi, Mwanthi Winfred; Ombuki, Charles; Nzioki, Susan (International Journal of Economics, Commerce and Management, 2019)
Conducting Performance Appraisal (PA) affects performance of commercial banks. When undertaking PA, banks should ensure that, the supervisors and employees know the parameters to be used in measuring the actual performance against the set targets at the start of the period. They should also be made to know the importance of PA both to individual employee and for the company and should be conducted periodically. This study sought to establish how conducting PA affects performance of commercial banks. The study was done in Machakos County in Kenya, in Africa. Data was collected from 16 commercial banks in the county. Sample size for the study was one hundred and ninety-five (195) respondents. A descriptive survey design was adopted. The research instruments used were questionnaire and interview guide, the former having closed-ended Likert scale questions and the later had guiding questions. Data was analyzed quantitatively and qualitatively using Statistical Package of Social Sciences (SPSS). The study found that there is a positive relationship between conducting performance appraisal and performance of commercial banks in Machakos County. The study also recommends that banks should use combination of appraisal techniques to reduce the weaknesses of one single technique. Continuous assessment of the methods used should be done.
Keywords: Performance, Performance Appraisal, Conducting, Parameters